Resultados perinatales adversos según la via de parto de los embarazos gemelares atendidos en el Hospital Regional Docente de Trujillo durante los años 2011 - 2015 - Zamora Chávez, Rocio Del Pilar (2018)
To evaluate if there is a difference between the perinatal results according to the delivery route of the twin pregnancies attended in the Regional Teaching Hospital of Trujillo during the years 2011-2015. Materials and Methods: Observational, analytical, comparative and retrospective study in pregnant women with twin pregnancies that were attended in the Obstetrics Service of the Teaching Regional Hospital of Trujillo from 2011-2015. The G1 groups (66 pregnant women with vaginal delivery) and G2 (132 pregnant women with cesarean delivery) were compared according to the maternal-fetal characteristics of the newborn and the adverse perinatal results of each of the twins. The statistical analysis was performed using the Z or T-student test. These tests were considered significant if p <0.05. Results: The average maternal age was 28.4 in the G1 group vs 27.8 in the G2 group; the mean of the weeks of gestation was 36.5 in the group G1 vs 36.3 in the group G2. The preterm delivery was more frequent and with significant result in the group G2. The small ones for the gestational age (PEG) were higher in the group G2 with significant difference in the second twin. According to the type of fetal presentation, in the G1 group, the highest frequency and with a significant result was the cephalic-cephalic type, unlike the G2 group, which was the polalic-cephalic and podal-podal type. The adverse perinatal results were more frequent. in group G2, finding a significant difference in Apgar at minute <7 and in low birth weight (LBW) with respect to the first twin; in the G1 group, the second twin at birth showed significantly Apgar at 5 minutes less than 7 compared with the first twin. Conclusions: Whether there was a difference in some of the adverse perinatal outcomes according to the route of delivery for both twins